PENGEMBANGAN MODUL BERBANTUAN DENGAN PENGEMBANGAN MEDIA MAKET PADA PEMBELAJARAN BIOLOGI KELAS X SMAN 2 BATUSANGKAR - Putri, Aulia; Eliwatis, Eliwatis; Kurnia Fitri, Dwi Rini (Jurnal Pembelajaran MIPA, 2014)
The purpose of this paper is get a product module assisted maket media that valid and practic. Kind of research was used in this Research of Development. Model of development were used are 4-D, they are define, design, developÂ  and disseminate. Prosedure of research have been done in there phase, they are phase front-end analysis, prototype phase and assessment phase.Â  Base of research was know module assisted maket media have got valid. Result test praktikalitas via questionnaire responds, observation and interview, module assisted maket media is practic. Indeed, quality of product development was conducted valid and practical bases on the result validate and praktikalitas have been done.Key words: development, module, maket media, biology learning